The Difficulty Level of Online Learning Content According to the Students' Perspective towards Arabic Language Course - Hairun Najuwah Jamali; Ku Fatahiyah Ku Azizan; Awatif Abdul Rahman; Wazzainab Ismail (Proceeding of International Conference on Islamic Education, 2021)
Online teaching and learning is no longer an option as a result of the corona virus pandemic, also known as COVID-19. Since March 2020, teaching and learning activities in all educational institutions at various levels are implemented online. Therefore, this paper discusses the findings of a study that has been conducted quantitatively on 295 undergraduate students at Kolej Universiti Islam Antarabangsa Selangor (KUIS). This study aims to discover the difficulty level of online learning content according to the students' perspective towards Arabic language courses NBWU1062 Al Arabiah Al A’liyah Li Dirasat Islamiyyah II and NBWU2102 Al Arabiah Al A’liyah Li Dirasat Islamiyyah III. The learning content consists of listening, speaking, reading and writing skills as well as grammar learning. The findings of the study shows that the most difficult level of learning content is listening skills and the easiest level is reading skills. The study aims to help the lecturers involved in teaching this course to further improve the quality of teaching and learning in the future.